COMPARATIVE CONSUMER PERCEPTIONS TO PURCHASE DECISIONS OF DRINKING WATER IN PACKED BRAND LE MINERAL AND AQUA IN TIKUNG, LAMONGAN REGENCY - Nurcholidah, Lilik; Sulaeman, Moh. Muklis (UNIVERSITAS PAKUAN, 2021)
By knowing consumer perceptions, companies can prepare new strategies and make comparisons by obtaining a lot of information from consumers. Companies can find out many things from consumer perceptions, one of which is knowing the advantages of competing products, the shortcomings of their own products. So that the company more quickly anticipates its shortcomings and makes improvements. The purposes of this study are (1) to determine the comparison of consumer perceptions of the decision to purchase bottled drinking water with the brand Le mineral and Aqua in the Tikung sub-district, Lamongan Regency (2) To determine the most dominant consumer purchased between drinking water in the brand Le mineral and Aqua. on purchasing decisions in the Tikung sub-district, Lamongan Regency. In this study, there were 1,105 consumers who consumed bottled drinking water with the brand Le mineral and Aqua at the UD Barokah store, Tikung sub-district, Lamongan Regency. The sample in this study were 100 respondents. Sampling in this study were people or consumers who had bought bottled drinking water with the brand Le mineral and Aqua at the UD Barokah Store. Based on a comparative descriptive analysis of consumer perception variables which include price and product quality indicators, there are significant differences in consumer perceptions between Le Minerl Le and Aqua on purchasing decisions in Tikung Lamongan District.